2017
DOI: 10.1002/ddr.21389
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gabapentin and Tramadol in Cancer Pain Induced by Glioma Cell in Rat Femur

Abstract: Preclinical Research The presence of pain as part of the cancer process is variable. Glioblastoma multiform (GBM) can produce bone metastasis, a condition that involves other pathological phenotypes including neuropathic and inflammatory pain. Tramadol and gabapentin are drugs used in the treatment of neuropathic pain. However, there are no studies evaluating their analgesic effects in bone metastasis. We produced a pain model induced by the inoculation of glioma cells (10 ) into the rat femur, by perforating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Tramadol is used alone or in combination with other narcotics for neuropathic and inflammatory pain treatment. 32 , 58 Several investigations revealed that tramadol can alleviate BCP in rodent models and in humans 59 , 60 ; however, these studies failed to correlate the mechanism underlying the analgesic effect of tramadol on BCP with the purinergic signaling pathway. Based on the previous findings, 61 , 62 tramadol can rapidly penetrate the blood–brain barrier and blood–cerebrospinal fluid barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Tramadol is used alone or in combination with other narcotics for neuropathic and inflammatory pain treatment. 32 , 58 Several investigations revealed that tramadol can alleviate BCP in rodent models and in humans 59 , 60 ; however, these studies failed to correlate the mechanism underlying the analgesic effect of tramadol on BCP with the purinergic signaling pathway. Based on the previous findings, 61 , 62 tramadol can rapidly penetrate the blood–brain barrier and blood–cerebrospinal fluid barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of drug treatments for relieving cancer pain have been discovered, such as Scorpion (Yu et al, 2020), Morin (Jiang et al, 2017), XPro1595 (a soluble tumor necrosis factor [solTNF] inhibitor) (Zhou et al, 2019), Rolipram (Guo et al, 2016), Gabapentin and Tramadol (Corona‐Ramos et al, 2017), and P2X receptor antagonists (such as BBG [Wu et al, 2022] and A‐740003 [Li et al, 2018]). All of these methods are effective in relieving cancer pain.…”
Section: Scs and Cancer Pain Treatmentmentioning
confidence: 99%